Perceived barriers of physical activity among KOSPEN community in Putrajaya - M. N., Mohd Tariq; K. S., Hayati (Community Health Society Malaysia, 2018)
Background: In Federal Territory of Putrajaya, the prevalence of physical inactivity in 2015 was 32.5% compared to 2011 with 56.5%, as reported in National Health Morbidity Survey. Although various facilities have been provided in Putrajaya and was selected as a garden city concept town, the public do not use the facilities as much as they should. Only a few studies were conducted on perceived barriers of physical activity, especially in Malaysia.